ADVANCED MATERIALS AND FABRICATION METHODS FOR FLAME RETARDANT APPLICATIONS - Wojtal, Patrick (My University, 2016)
Investigation of flame retardant materials (FRM) identified materials as effective substitutes for halogenated FRM. Many promising materials were tested such as hydrotalcite-type Al–Mg–Zr complex hydroxide, huntite, aluminum hydroxide, hydrotalcite, magnesium carbonate hydroxide pentahydrate, magnesium sulfate heptahydrate, magnesium phosphate hydrate, magnesium chloride hexahydrate, sodium metasilicate pentahydrate, XZO 2022 (Mg3Al) and halloysite. Electrophoretic deposition (EPD) manufacturing technique has been developed for the fabrication of coatings containing the most promising FRM candidates. Identifying charging and dispersion agents, such as poly(4-vinylpyridine-co-butyl methacrylate), humic acid, 2,2′- biquinoline-4,4′-dicarboxylic acid, quaternized hydroxyethylcellulose ethoxylate, 3- phosphonopropionic acid, 16-phosphonohexadecanoic acid, octadecylphosphonic acid, celestine blue, chitosan, to facilitate EPD was of great importance for successful deposition of composite FRM films. The films were investigated using scanning electron microscopy, transmission electron microscopy, X-ray diffraction analysis, thermogravimetric and differential thermal analysis, as well as Fourier Transform Infrared and Ultraviolet-Visible spectroscopy.
Keywords: flame retardants; coatings